1998
DOI: 10.1093/ps/77.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Research notes: Immunohistochemical observations in the ceca of chickens infected with Salmonella enteritidis phage type four

Abstract: One-day-old specific-pathogen-free White Leghorn chicks were inoculated orally with Salmonella enteritidis phage type 4 to study adhesion and invasion of the ceca by immunohistochemistry. Positive staining bacilli were associated with the epithelial surface and were present in the lumen of the cecal crypts. They were observed in the interstitial tissue and in the cytoplasm of macrophage-like cells in the lamina propria. A granulomatous nodule containing positive staining bacilli was present in the submucosa of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Chemical bursectomy has the disadvantage that cell types other than only B cells may be affected. Colonization of liver and spleen decreased over time in control as well as in bursectomized animals, indicating that other immune mechanisms play a role in systemic clearance of S. Enteritidis in chickens (Desmidt et al , 1998c). By contrast surgically bursectomzed chickens, in which only B cell maturation would be affected, showed clearance of S. Typhimurium from the intestine at the same rate as nonbursectomized birds (Beal et al , 2006), demonstrating that antibody response is not essential to gut clearance which poses a number of fundamental and interesting questions about the nature and anatomical site/location of immune clearance.…”
Section: Immunity To Salmonellamentioning
confidence: 97%
See 2 more Smart Citations
“…Chemical bursectomy has the disadvantage that cell types other than only B cells may be affected. Colonization of liver and spleen decreased over time in control as well as in bursectomized animals, indicating that other immune mechanisms play a role in systemic clearance of S. Enteritidis in chickens (Desmidt et al , 1998c). By contrast surgically bursectomzed chickens, in which only B cell maturation would be affected, showed clearance of S. Typhimurium from the intestine at the same rate as nonbursectomized birds (Beal et al , 2006), demonstrating that antibody response is not essential to gut clearance which poses a number of fundamental and interesting questions about the nature and anatomical site/location of immune clearance.…”
Section: Immunity To Salmonellamentioning
confidence: 97%
“…Clearance of S. Typhimurium infection in chickens correlates with high cell-mediated responses (delayed type hypersensitivity reaction) and not with high antibody levels (Lee et al , 1981;Ib 1983). A study of Desmidt et al (1998c) with S. Enteritidis infected, chemically bursectomized chickens showed increased faecal excretion and higher caecal Salmonella counts, while having normal counts in internal organs, indicative of a protective effect of IgA against intestinal colonization. Chemical bursectomy has the disadvantage that cell types other than only B cells may be affected.…”
Section: Immunity To Salmonellamentioning
confidence: 99%
See 1 more Smart Citation
“…Our infection model was based on the previous studies, which showed that orally introduced S. enteritidis had a rapid transit time through the intestine and established itself within the walls of the gut in more than 3 d [17,18] . 80 mice (age 9 wk, specific-pathogen-free) were purchased from the Animal Center of Sichuan University, China.…”
Section: Experimental Infection Of Micementioning
confidence: 99%
“…Enteritidis results in attachment and entering of bacteria to the epithelial cells of intestinal villi (Asheg et al, 2003). After lysis of the host cells, bacteria are found in the lamina propria lying free or inside macrophage-like cells (Desmidt et al, 1998).…”
mentioning
confidence: 99%